An adult patient with previously undiagnosed sinus venosus atrial septal defect presenting with brain abscess: a case report. Issue 7 (26th July 2021) - Mathew, Navin; Hegde, Nischal N
Abstract: Background: Brain abscess is a common complication in children with cyanotic congenital heart disease. The presence of an underlying acyanotic congenital heart disease is usually not suspected in an adult patient presenting with brain abscess. Case summary: A 51-year-old male patient with no known co-morbidities came with complaints of recent onset right lower limb weakness needing support while walking and on evaluation was found to have brain abscess. He underwent robotic endoscope assisted endoport excision of the brain abscess. Two-dimensional transthoracic echocardiography showed right atrial and right ventricular dilatation with mild low-pressure tricuspid regurgitation. Transoesophageal echocardiography (TOE) revealed sinus venosus atrial septal defect (ASD) with left-to-right shunt with the right upper pulmonary vein draining into superior vena cava. Contrast echocardiography revealed a small transient right-to-left shunt. He has been advised to undergo elective surgical closure of ASD with partial anomalous pulmonary venous connection repair. Discussion: Right-to-left shunting in ASDs can occur in the early systole even in the absence of raised pressures in the right side of the heart, even when the predominant shunt is left to right, but the magnitude of such a shunt is small and transient and is easily missed. Contrast echocardiography and TOE should be done as a part of evaluation of patients presenting with brain abscess.